Identification of Food Avoidance Myths in Pregnant Women, Kedungwringin Village, Jatilawang District, Banyumas Regency - Masruroh, Umi (International Proceedings of Nusantara Raya, 2022)
The myth of dietary taboos in Indonesia is still a problem because there are still many foods that should be consumed but are prohibited. The basis of food habits is characterized in a person's value system in choosing foods that can be consumed and should not be consumed. The value system is based on religious sources and belief in God, customs that come from ancestors. This study aims to identify the myths of dietary taboos for pregnant women in Kedungwringin Village, Jatilawang District, Banyumas Regency. This study uses a descriptive culture studies method using an anthropological approach that does not require scientific proof. Data collection techniques used in this study using interview, observation, recording and documentation techniques. The data analysis technique uses descriptive - analytical, which describes the existing data so that it becomes clear. This research was conducted in Kedungwringin Village, Jatilawang District, Banyumas Regency. The subjects in this study were residents of Kedungwringin Village, Jatilawang District, Banyumas Regency. The object of study in this study is the myth of food taboos for pregnant women. The myth of food taboos for pregnant women circulating in the village of Kedungwringin, Jatilawang District, Banyumas Regency is that pregnant women should not eat shrimp, catfish, soy leaf vegetables, attached bananas, cold water / ice because they are believed to have a bad impact on the baby they are carrying. This research on the myth of dietary taboos for pregnant women in the village of Kedungwringin, Jatilawang District, Banyumas Regency was studied using Roland Barthers' semiotic theory which was seen from the denotative and connotative meanings.